Optimization-based assessment of design limitations to air separation plant agility in demand response scenarios. (September 2015) - Cao, Yanan; Swartz, Christopher L.E.; Baldea, Michael; Blouin, Stéphane
Abstract : Highlights: First-principles DAE model of industrial air separation unit. Two-tiered formulation to determine optimal economic operating point and measure of minimum transition time. Identification of design limitations to air separation plant agility. Assessment of effect of design modifications on plant transition speed. Abstract: The significant effect that the design of a plant can have on its dynamic performance has led to methodologies for systematic analysis of the interaction between design and control, and for inclusion of dynamic performance considerations in plant design. This article focuses on the assessment of design limitations to the agility of a nitrogen plant in response to demand and electricity price fluctuations. A two-tiered approach is proposed, where an economics-based optimization problem is first solved to determine the optimal steady-state operating point, after which a dynamic optimization problem is solved to minimize a measure of the transition time to the new operating point. Design limitations to the plant's responsiveness may be inferred by analysis of the active constraints. The approach is demonstrated on a comprehensive case study based on an existing industrial nitrogen plant. The design limitations of the existing plant configuration are identified, and the potential benefits of selected design modifications to demand response operation are assessed.